The Incidence of Ischemic Cholecystitis after Prophylactic Cystic Artery Embolization: A Single-Center Retrospective Study - Walker, Benjamin J.; Lung, Michael; Lataifeh, Hanin; Patel, Aditi; Abukhiran, Ibrahim; Amarneh, Mohammad (The Arab Journal of Interventional Radiology, 2023)
Background Prophylactic cystic artery embolization (CAE) is used to prevent radiation cholecystitis in patients undergoing transarterial radioembolization (TARE), but the incidence of ischemic cholecystitis following CAE remains unclear.Purpose This retrospective study aimed to determine the incidence of ischemic cholecystitis after prophylactic CAE prior to TARE.Methods The medical records of 22 patients who underwent CAE prior to TARE between 2002 and 2021 were reviewed. Patients were assessed for evidence of acute cholecystitis and gallbladder imaging changes after the procedure.Results Four out of the 22 patients (18.2%) developed cholecystitis after CAE, and two of these patients showed evidence of microsphere deposition consistent with radiation cholecystitis. Excluding these two patients, the incidence of ischemic cholecystitis was 9.1%. Additionally, 8 out of 22 patients (36.4%) developed gallbladder imaging changes after the embolization.Conclusion The incidence of ischemic cholecystitis following CAE is comparable, if not greater than the risk of radiation cholecystitis without prophylactic embolization. Further research is necessary to better understand the risk factors associated with the development of cholecystitis after CAE and to inform recommendations for future preventative measures.
Keywords: ischemic cholecystitis; cystic artery embolization; complications